2018
DOI: 10.4236/ijg.2018.94015
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Monsoon Depressions on Intraseasonal Oscillations over Indian Sub-Continent

Abstract: Summer monsoon and its synoptic, meso-scale systems provide 80% of total annual rainfall over India. Monsoon depressions are weak, low-pressure circulation within the monsoon trough that forms in the head Bay of Bengal and moves northwestward and westward across the Indian sub-continent during summer monsoon season. Another convective system from this planetary scale circulation is the Intraseasonal Oscillation (ISO) also occurs in the daily mode. It is very important to study the impact of monsoon depressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…(2014) argued the reason for north‐westward propagation (based of 100 MD analysis) could be due to adiabatic nonlinear advection of potential vorticity maximum (at 500 hPa). The previous study has also observed the warming in the equatorial Indian Ocean due to the presence of anomalous sea surface temperature, which plays an essential role in the genesis of MD (Suneetha et al ., 2018). Some other studies (e.g., Rao, 1971; Krishnamurti et al ., 1976; Sikka, 1977) have found that dynamic instability through wind shear (vertical and horizontal) associated with large scale flow could be the significant reason for MD growth; however, Ditchek et al .…”
Section: Introductionmentioning
confidence: 99%
“…(2014) argued the reason for north‐westward propagation (based of 100 MD analysis) could be due to adiabatic nonlinear advection of potential vorticity maximum (at 500 hPa). The previous study has also observed the warming in the equatorial Indian Ocean due to the presence of anomalous sea surface temperature, which plays an essential role in the genesis of MD (Suneetha et al ., 2018). Some other studies (e.g., Rao, 1971; Krishnamurti et al ., 1976; Sikka, 1977) have found that dynamic instability through wind shear (vertical and horizontal) associated with large scale flow could be the significant reason for MD growth; however, Ditchek et al .…”
Section: Introductionmentioning
confidence: 99%